2020
DOI: 10.3390/rs12183000
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Carbon Sequestration Mapping in Herbaceous Wetlands by Using a MODIS EVI Time-Series Data Set: A Case in Poyang Lake Wetland, China

Abstract: The carbon sequestration capacity of wetland vegetation determines carbon stocks and changes in wetlands. However, modeling vegetation carbon sequestration of herbaceous wetlands is still problematic due to complex hydroecological processes and rapidly changing biomass carbon stocks. Theoretically, a vegetation index (VI) time series can retrieve the dynamic of biomass carbon stocks and could be used to calculate the cumulative composite of biomass carbon stocks during a given interval, i.e., vegetation carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The results of the organic carbon storage estimation in GGW Senegalese soils show an upward dynamic in carbon sequestration for the reforested sites of Syer, Tessekere (Louga), Loughere-Thioly (Matam) and a loss capacity to store carbon on non-reforested sites (case of Ballou in Tambacounda region) over the period 1992-2020. Other works ( [17] [50]) had shown a positive dynamic of reforested sites based on vegetation indices (NDVI and VHI). The results of these studies reinforce ours on the positive dynamics of carbon sequestration observed in the different reforested soils of the GGW.…”
Section: ) Analysis Of Estimated Carbon Storage On Senegalese Gmv Sitesmentioning
confidence: 99%
“…The results of the organic carbon storage estimation in GGW Senegalese soils show an upward dynamic in carbon sequestration for the reforested sites of Syer, Tessekere (Louga), Loughere-Thioly (Matam) and a loss capacity to store carbon on non-reforested sites (case of Ballou in Tambacounda region) over the period 1992-2020. Other works ( [17] [50]) had shown a positive dynamic of reforested sites based on vegetation indices (NDVI and VHI). The results of these studies reinforce ours on the positive dynamics of carbon sequestration observed in the different reforested soils of the GGW.…”
Section: ) Analysis Of Estimated Carbon Storage On Senegalese Gmv Sitesmentioning
confidence: 99%
“…Carbon sequestration is observed as the process of determining the amount of carbon released as it indicates the changes reflected in the ecosystem. With the help of vegetation indices, it will help find the vegetation carbon sequestration (Dai et al 2020).…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…About 10 VIs (Table 2) were analyzed as predictor variables for AGB and Corg. Among the VIs, NDVI is often used to estimate vegetation biomass in wetlands 33,67 and in studies related to photosynthesis, carbon stocks, water balance, and other plant-related processes. This VI is sensitive to green leaf vegetation and photosynthetically active radiation.…”
Section: Vegetation Indicesmentioning
confidence: 99%